Grounding the Connection Between Psyche and Soma: Creating a Reliable Observation Tool for Grounding Assessment in an Adult Population - Shuper Engelhard, Einat; Pitluk, Michal; Elboim-Gabyzon, Michal (Frontiers in Psychology, 2021)
The concept of grounding is accepted and common among dance movement therapists and body psychotherapists. It expresses a stable physical and emotional presence - "supported by the ground." The assumption is that embodied emotional knowledge is expressed through the manner of physical holding and in the emotional experience in the world. However, along with the clinical use of the term, an empirical tool for examining grounding is lacking. The goal of the study was to examine the reliability and validity of an observation tool for assessing the quality of grounding, the Grounding Assessment Tool (GAT), which was created for the present study on the basis of theory, research and clinical knowledge in the field. Forty-four adult participants (age, M = 28.2 years, SD = 8.54) were recruited for an experimental and controlled session, the session included guided movement for approximately 10 minutes. The movement was recorded on video. The quality of the movement was rated by two raters and was scored using the GAT. The study findings indicated that the GAT is a reliable and valid tool - with good internal consistency (α = 0.850) and high interrater and intrarater reliability (Kendall’s 'range from 0.789 to 0.973 and intraclass correlation coefficient range from 0.967 to 1.00, respectively). The exploratory factor analysis showed that four factors are involved in the assessment of grounding quality: fluid and rhythmic movement, emotional expression in movement, pattern of foot placement, and lack of stability and weightiness. The results of this study expand the theoretical understanding of the concept of grounding. They contribute to the understanding of the benefits of body focus, dance and movement in psychotherapy and to validating body psychotherapy and dance movement therapy (DMT). The existence of a reliable and valid tool is essential for assessment and diagnostic processes, for formulating therapeutic goals focused on the body and for examining their effectiveness.